1992
DOI: 10.1063/1.462087
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-emission study of continuum Raman and the photofragmentation mapping of IBr

Abstract: Experiments and theory of the excitation-frequency dependence of the continuum-Raman signal of IBr are described. The theoretical computations, which do not follow the Kramas–Heisenberg expression, are extremely successful in predicting the wavelength dependence of each Stokes line and the ratio between the different overtones. The ‘‘reflection principle’’ or ‘‘photofragmentation mapping’’ of absorption spectroscopy, which postulates the equivalence between the topology of an initial vibrational wave function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…2͑c͒ and 2͑d͒ discussed earlier where the molecule when described by 2 max is placed on the steeper part of the excited curve and In contrast, the smoothness of the absorption spectrum from 2 max as the initial condition stems from the initial placement of the 2 max wave packet on the steeper part of the excited curve which facilitates faster diabatic exit with little time for interference. The absorption spectrum from 0 as the initial condition has also been plotted and compares well with other calculated 39,40 and experimental 42,43 absorption spectra for IBr. The absorption spectra peak at the wavelengths corresponding to the vertical Franck-Condon transition energies with 1 max , 2 max , and 0 as the initial states.…”
Section: A Ibrmentioning
confidence: 98%
See 1 more Smart Citation
“…2͑c͒ and 2͑d͒ discussed earlier where the molecule when described by 2 max is placed on the steeper part of the excited curve and In contrast, the smoothness of the absorption spectrum from 2 max as the initial condition stems from the initial placement of the 2 max wave packet on the steeper part of the excited curve which facilitates faster diabatic exit with little time for interference. The absorption spectrum from 0 as the initial condition has also been plotted and compares well with other calculated 39,40 and experimental 42,43 absorption spectra for IBr. The absorption spectra peak at the wavelengths corresponding to the vertical Franck-Condon transition energies with 1 max , 2 max , and 0 as the initial states.…”
Section: A Ibrmentioning
confidence: 98%
“…In any case, treatment of rotational effects will increase the computational complexities by at least an order of magnitude 37 and we have therefore found it judicious to neglect rotational motion in this initial application. Photodissociation of IBr 21,26,[38][39][40][41][42][43] and HI [9][10][11][12][13][14][15][16]20 have been studied extensively and are our representative systems of choice. In the following section we analyze some representative max (0) for IBr and HI to investigate the mechanistic underpinning of photodynamic control of product selectivity and yield.…”
Section: ͑9͒mentioning
confidence: 99%
“…Nonadiabatic wave packet studies in diatomic molecules have been carried out on systems such as NaI, where two diabatic potential energy curves are strongly coupled 2,[9][10][11][12][13] and, in our previous studies, on the IBr molecule. [14][15][16] The latter represents the interesting case of intermediate coupling: a complete failure of the Born-Oppenheimer approximation where the wave packet evolution cannot be described by either the diabatic ͑weak coupling͒ or adiabatic ͑strong coupling͒ approximations. 17,18 In this article, we present details of a combined experimental-theoretical study of wave packet dynamics in IBr.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In this communication, we present experimental fs pump-probe studies on the IBr molecule, where a complicated wave packet evolution is observed which cannot be described exclusively by either the diabatic ͑weak coupling͒ or adiabatic ͑strong coupling͒ pictures. [8][9][10] In Fig. 1 both diabatic ͑dashed lines͒ and adiabatic ͑solid lines͒ potential energy curves are shown for the IBr molecule.…”
mentioning
confidence: 99%